1990
DOI: 10.1093/ndt/5.11.920
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Deficiency in Acute Renal Failure

Abstract: Erythropoietin (Epo) was sequentially measured by radioimmunoassay in 11 patients with acute renal failure (ARF) of varied aetiology. Epo rapidly decreased to a level inappropriately low for the haemoglobin, the reduced Epo value persisting throughout the oliguric phase and for up to 2 weeks after the restoration of apparently normal renal function. Epo values found in ARF were: at referral 18.2 +/- 9.5, mid-oliguria 14.4 +/- 6.8, diuresis 15.6 +/- 5.8, and recovery 25.1 +/- 15.8 mU/ml. Results are compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Upon admission, this deficit varied from small to severe; after the first transfusion, and with persistence of during the recovery phase, as the excretory capacity recovered, EPO levels increased, but not to normal values. This difference in the recovery of excretory and endocrine functions was similar to that described by Lipkin et al [2] and Heidenreich et al [3] in adults with ARF.…”
Section: Discussionsupporting
confidence: 89%
“…Upon admission, this deficit varied from small to severe; after the first transfusion, and with persistence of during the recovery phase, as the excretory capacity recovered, EPO levels increased, but not to normal values. This difference in the recovery of excretory and endocrine functions was similar to that described by Lipkin et al [2] and Heidenreich et al [3] in adults with ARF.…”
Section: Discussionsupporting
confidence: 89%
“…In compromised renal function, such as chronic renal failure and end stage renal disease, patients suffer from severe anemia because RBC production is reduced because of the inability of the kidneys to produce sufficient amounts of Epo to maintain RBC homeostasis (4,5). Here, we observed that a lack of Fgf-23 results in markedly augmented erythropoiesis in PB and BM that can be accounted for by elevated levels of HIF and Epo in BM, liver, and kidney, which can also lead to increased HSC frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CKD are often diagnosed with severe anemia because of the inability of their kidneys to produce erythropoietin, the hormone responsible for red blood cell (RBC) production in the BM in response to low oxygen levels in the blood (4,5). Additionally, CKD patients also suffer from osteopenia, osteoporosis, or osteomalacia, giving rise to the term "chronic kidney disease-mineral bone disorder," affirming a link between mineral metabolism and kidney function.…”
mentioning
confidence: 99%
“…When the EPO response to anaemia is compared with the normal response that oc-161 Values are mean ± SEM * p < 0.05 vs group 1 † p < 0.05 vs group 5 Fig. EPO deficiency may be expected in acute, as in chronic, renal failure and has been reported in small studies [18,19]. In each graph the standard regression line derived from the control group is represented by a bold line (ARF acute renal failure) curs in ambulatory patients with iron-deficiency anaemia, an inadequate response in critically ill patients becomes evident.…”
Section: Discussionmentioning
confidence: 99%